Programma: 8 oktober: Switi hot! Kasekeo Music; 9 oktober: Caribeyo Salso Show Groep; 10 oktober: Candy Dulfer & Funky Stuff; 12 oktober: Buzzcocks (1993)
Programma: 8 oktober: Switi hot! Kasekeo Music; 9 oktober: Caribeyo Salso Show Groep; 10 oktober: Candy Dulfer & Funky Stuff; 12 oktober: Buzzcocks.